Transparent TiO2 nanotubes on zirconia for biomedical applications. Issue 48 (12th June 2017) - Patel, Sweetu B.; Baker, Natalie; Marques, Isabella; Hamlekhan, Azhang; Mathew, Mathew T.; Takoudis, Christos; Friedrich, Craig; Sukotjo, Cortino; Shokuhfar, Tolou
Abstract : Depositing anodised titanium on ZrO2 substrate improves the bioactivity of the ZrO2 substrate in terms of enhanced cell viability, cell attachment and cell elongation. Abstract : Tissue discoloration in dental implant patients with thin gingival tissue is one of the many causes of dental implants' revision surgery. Therefore, the purpose of this study is to address this issue by developing a surface that has a "tooth like bright colored" appearance while at the same time enhancing the bone implant integration. A biomimetic surface is fabricated by forming transparent TiO2 nanotubes on zirconia (TTNZ) that can enhance the proliferation and attachment of human mesenchymal stem cells (hMSCs) as compared to roughened ZrO2 . This surface treatment was aimed to resolve tissue discoloration and aesthetic appearance problems for dental implant patients, while also enhancing biocompatibility. TiO2 nanotubes (TNTs) were formed using an electrochemical anodization technique in an electrolyte comprised of NH4 F, ethylene glycol and water. The presence of TNTs on the ZrO2 substrate was detected by field emission scanning electron microscopy (FESEM). Optical images of longer anodized (20 and 30 min) samples show the white colored appearance characteristic of ZrO2 and FESEM confirmed the presence of TNTs on anodized samples. Surface characteristics of all samples were analyzed using water contact angle analysis, Fourier-transform infrared spectroscopy, white light interferometry and FESEM. Quantitative and qualitative biocompatibility analysis of treated and non-treated ZrO2 surfaces were obtained by performing FESEM, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2 H -tetrazolium bromide (MTT) assay and fluorescence microscopy. FESEM revealed well-elongated and well-spread cell morphology on the nanotubular surface as compared to roughened ZrO2 . Additionally, MTT assay showed a significantly high cell proliferation for anodized Ti–ZrO2 surface as compared to roughened ZrO2 after 7 days of incubation.